PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASI PADA PT. PELABUHAN INDONESIA I (PERSERO) MEDAN - Damrus Damrus; Ronal Donra Sihaloho (universitas teuku umar, 2018)
Abstract : Organizational commitment is one of the important thing to be considered by the company to observe the extent to which employees are responsible toward their responsibility merupakan suatu hal yang penting untuk diperhatikan suatu perusahaan untuk melihat sejauh mana karyawan tersebut lebih bertanggungjawab terhadap kewajibannya. PT. Pelabuhan Indonesia I (Persero) Medan engage in port services which has good performance. However, on March-August 2015 the employees performance of PT. Pelabuhan Indonesia I (Persero) Medan showed declining trend. This declining in performance are assumed to be influenced by several factors such as work stress and organizational commitment. This study aims to analyse the influence of work stress toward organizational commitment at PT. Pelabuhan Indonesia I (Persero) Medan. The problem identification of this study is how to increase the organizational commitment by considering work stress inside the company. The theory used in this study is human resources management related to work stress and organizational commitment. The method used in this study is survey method, this is descriptive quantitative study ant the nature of this study is explanatory research. The number of samples used in this study are 72 people. The samples are drawn by using non probability sampling technique with purposive sampling method. Data analysis method used is simple multiple linear regression analysis using SPSS software. The result shows that partially wotk stress conflict has negative and significant influence toward organizational commitment. Key words: Stres kerja dan Komitmen organisasi